Passenger Perceptions towards Service Quality of Airlines Based in Singapore - Hamid, M. Syamil Bin Shahul; Baxter, Glenn; Wild, Graham (International Review of Management and Marketing, 2021)
This research focuses on understanding how passengers had perceived airline’s flight services as well as how passengers had evaluated the importance of service quality dimensions of airlines based in Singapore, specifically understanding whether full-service network carriers or low-cost carriers had delivered better value-added service quality in terms of whether airfares were value for money, as well as identifying whether gender and age differences perceive differently towards service quality. Data was collected via a survey at Singapore’s Changi Airport, targeting arriving passengers who had flown on Singapore-based airlines. The results revealed that full-service network carriers had delivered better value in flight services as compared to low-cost carriers. The results also highlighted that between genders, male passengers are more satisfied with airline’s flight services as compared to females, while between age groups, significant differences were found in overall seat comfort. Moreover, Airline safety records and on-time departure and arrival followed by lavatories cleanliness and odourless were rated as the most important factors towards passengers. Keywords: Airfares, Service quality assessment, SERVQUAL, Singapore-based airlines, Value-added service JEL Classifications: L93, M30, M31 DOI: https://doi.org/10.32479/irmm.9096